2017
DOI: 10.1186/s40001-017-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic joint infection development of an evidence-based diagnostic algorithm

Abstract: BackgroundIncreasing rates of prosthetic joint infection (PJI) have presented challenges for general practitioners, orthopedic surgeons and the health care system in the recent years. The diagnosis of PJI is complex; multiple diagnostic tools are used in the attempt to correctly diagnose PJI. Evidence-based algorithms can help to identify PJI using standardized diagnostic steps.MethodsWe reviewed relevant publications between 1990 and 2015 using a systematic literature search in MEDLINE and PUBMED. The selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 115 publications
0
20
0
3
Order By: Relevance
“…They occur as a result of contamination during or immediately after surgery or at later periods following hematogenic spread [1][2][3]. Numbers of implantations, in general, are growing because of an aging population, increasing obesity, and other predisposing factors [4][5][6][7]. In addition, worldwide rising bacterial resistance against antibiotics [8][9][10][11] and further, the irreversible adhesion of bacteria and production of extracellular matrix in biofilm formation on the implant surface (infection cause) complicate a successful treatment [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They occur as a result of contamination during or immediately after surgery or at later periods following hematogenic spread [1][2][3]. Numbers of implantations, in general, are growing because of an aging population, increasing obesity, and other predisposing factors [4][5][6][7]. In addition, worldwide rising bacterial resistance against antibiotics [8][9][10][11] and further, the irreversible adhesion of bacteria and production of extracellular matrix in biofilm formation on the implant surface (infection cause) complicate a successful treatment [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the plasma CRP level is recommended for the diagnosing of prosthetic joint infection [8]. Kim et al [9] showed that a high preoperative CRP level (> 100 mg L -1 ), a history of malignancy, a high ASA PS grade, and postoperative ICU admission were predominant risk factors for 1-year mortality after hip surgery in geriatric patients.…”
Section: The Dependence Of Drainage Blood Crp Levels On the Methods Ofmentioning
confidence: 99%
“…Die Indikation zur Zupfbiopsie wurde anhand eines vom Autorenteam bereits publizierten evidenzbasierten Algorithmus zur Abklärung chronisch schmerzhafter Knieprothesen und nicht auszuschließender Low-Grade-Infektion durchgeführt (▶ Abb. 1) [32]. Der Algorithmus wird mittlerweile seit 3 Jahren an unserer Klinik eingesetzt.…”
Section: Evidenzbasierter Algorithmusunclassified
“…Die Indikation zur Zupfbiopsie war bei Vorliegen einer chronisch (> 6 Monate) schmerzhaften Knieprothese ohne Hinweis auf eine mechanische Ursache (Ausschluss Rotationsfehler im Rotations-CT, Stressröntgenaufnahme mediolateral in 20°Flexion bzw. a.-p. in 90°Flexion ohne Hinweis für höhergradige Instabilität), dem Vorhandensein von Risikofaktoren für eine PPI und einem negativen Keimnachweis nach Punktion des Gelenks gegeben [32]. Die Kniegelenkpunktion erfolgte zuvor als ambulanter Eingriff in den klinikeigenen Ambulanzräumen unter sterilen Kautelen.…”
Section: Präoperative Diagnostikunclassified
See 1 more Smart Citation